Legal Certainty for Creditors Holding Second-Ranking and Subsequent Mortgage Rights in Execution Auctions - Diah Kusumo Dewi; Amelia Sri Kusuma Dewi; Satria Amiputra Amimakmur (Faculty of Law, Merdeka University Surabaya, Indonesia, 2027)
There is a normative gap between the legal recognition of second-ranking mortgage rights as provided under Article 5(1) of the Mortgage Law and the implementation of their execution rights in auction practice, particularly due to the rejection of auction applications submitted by the Office of State Assets and Auction Services (KPKNL) on behalf of creditors holding second-ranking and subsequent mortgage rights. This study aims to analyze the juridical implications of Article 5(1) of the Mortgage Law for the legal position of creditors holding second-ranking and subsequent mortgage rights in the execution auction of mortgaged property, as well as to examine the legal protection afforded to such creditors. This research employs a normative legal research method using both the statutory and conceptual approaches through the analysis of legislation, legal doctrines, and other relevant legal materials. The findings reveal that although Article 5(1) of the Mortgage Law explicitly recognizes the existence of second-ranking and subsequent mortgage rights, it does not adequately regulate the mechanism for exercising execution rights or provide comprehensive legal protection for subordinate mortgage creditors. Consequently, the execution auction process continues to be hindered by divergent interpretations regarding execution authority, resulting in the potential rejection of auction applications filed by creditors holding second-ranking and subsequent mortgage rights. The novelty of this study lies in proposing a harmonized regulatory framework governing execution authority and a legal protection mechanism for creditors holding second-ranking and subsequent mortgage rights, thereby providing a foundation for the reform of Indonesian secured transactions law.